URGENSI PENERAPAN MANAJEMEN MUTU DALAM MENINGKATKAN KUALITAS PEMBANGUNAN INFRASTRUKTUR (KAJIAN LITERATUR) - Eliyanti Agus Mokodompit; Muh. Faisal Sahlan; Rifan Afandi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to analyze the role of quality management in improving the quality of infrastructure development through a literature review approach. The data were collected from various sources, including national and international journal articles, textbooks, and relevant research reports related to quality management and infrastructure construction. The findings indicate that quality management plays a strategic role in ensuring the success of construction projects, particularly in enhancing work quality, cost efficiency, timeliness, and infrastructure sustainability. The effectiveness of quality management implementation is strongly influenced by the quality of human resources, organizational commitment, and the consistent application of established quality standards. In addition, control and testing are identified as the most dominant variables in improving project performance. This is because these aspects function as the primary instruments for ensuring conformity between technical specifications, implementation processes, and the quality of work results. Effective control and testing can minimize project failure risks and ensure optimal infrastructure quality.